Effectiveness of RME Model Using Rocket Miniset Manipulatives on Fraction Understanding in Elementary School Students - Supratman, Ujang Supratman; Harianingsih Harianingsih; Decky Avrilianda; Ellianawati Ellianawati (Elementary Teacher Education Program, Majalengka University, 2025)
The comprehension of the concept of fractions represents a fundamental challenge in the domain of mathematics, persisting even at the elementary school level. The challenges encountered in comprehending fractions frequently stem from the manner in which abstract concepts are conveyed and the pedagogical approaches employed, which do not effectively align with students' experiential knowledge. The objective of this study is to assess the efficacy of the Realistic Mathematics Education (RME) model, which utilizes rocket mini-set manipulative media, in fostering comprehension of the concept of fractions among grade V elementary school students. The research employed a quantitative approach, utilizing a quasi-experimental design of the pretest-posttest control group type. The subjects of the research study were divided into two groups: an experimental group that learned using the RME model with rocket mini-set media and a control group that used conventional learning methods. The instruments utilized in this study encompassed both written tests and observation sheets. The findings indicated a substantial discrepancy in the mean posttest scores between the experimental and control groups. Learners who were instructed via the RME model, which is predicated on rocket mini-manipulative media, demonstrated a greater increase in their comprehension of fraction concepts in comparison to learners who were instructed via conventional methods. This finding indicates that the incorporation of manipulative media within the RME approach facilitates a more meaningful and contextual learning experience for students, thereby assisting them in comprehending mathematical concepts more concretely. The present study offers the following recommendations.